1386Ethnic differences in lifestyle interventions for diabetes prevention: a systematic review and meta-analysis. (2nd September 2021) - Chen, Mingling; Ukke, Gebresilasea; Sood, Surbhi; Bennett, Christie; Khomami, Mahnaz; Moran, Lisa; Harrison, Cheryce; Absetz, Pilvikki; Teede, Helena; Lim, Siew
Abstract: Background: The risk of type 2 diabetes varies by ethnicity, but ethnic differences in response to lifestyle interventions for diabetes prevention remain unclear. This systematic review and meta-analysis aimed to assess differences in the effects of lifestyle interventions on diabetes incidence, glycemic outcomes and anthropometric measures between ethnic groups. Methods: MEDLINE, EMBASE, Pubmed, CINAHL, PsycInfo and EBM Reviews were searched (to June 2020) with no language restriction for randomized and non-randomized controlled trials on lifestyle interventions involving diet and/or physical activity in adults at risk of type 2 diabetes. Ethnicity was categorized into European, South Asian, Other Asian, Middle Eastern, Latin American and African groups based on the World Bank regions. Risk ratios for diabetes incidence and mean differences for glycemic outcomes (fasting glucose, 2-h glucose, HbA1c ) and anthropometric measures (weight, BMI, waist circumference) were pooled using random-effects meta-analysis. Results: Sixty articles representing 43 studies (18, 691 participants) were included in meta-analyses. Overall, lifestyle interventions resulted in significant improvement in diabetes incidence, glycemic outcomes and anthropometric measures compared with controls (all P <0.01). Significant subgroup differences by ethnicity were found for 2-h glucose, weight, BMI and waist circumference (all P <0.05) but not for diabetes incidence, fasting glucose and HbA1c (all P >0.05). Conclusions: Lifestyle interventions are similarly effective in reducing diabetes incidence, fasting glucose and HbA1c for all ethnic groups, however, 2-h glucose and anthropometric outcomes should be optimized in certain ethnic groups. Key messages: Lifestyle intervention is likely effective in preventing the progression to type 2 diabetes equally across all ethnic groups.